OVERCOMING ADOLESCENT ANXIETY THROUGH RELIGIOUS EDUCATION: AN ISLAMIC LITERATURE REVIEW - Mega Nur Safira; Sabran Sabran (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Adolescence is a developmental stage that is highly vulnerable to anxiety due to academic pressures, social challenges, and identity crises. Conventional approaches to addressing anxiety do not always meet the spiritual needs of adolescents, especially in societies that uphold religious values. This study aims to explore the role of Islamic religious education in helping adolescents manage anxiety. The method employed is a qualitative literature study with a descriptive-reflective approach, focusing on the analysis of religious and spiritual values related to mental health. The findings reveal that Islamic religious education contains values such as tawakkul (trust in God), sabr (patience), shukr (gratitude), dhikr (remembrance of God), and du'a (supplication), which function as emotional coping strategies. These values contribute to building adolescents' mental resilience, calming emotions, and strengthening their sense of meaning and purpose in life. Through a more contextual and practical approach, religious education can serve as an effective alternative intervention to support adolescents’ mental health in a holistic manner.